Effect of pore network characteristics on non-Darcy permeability of pervious concrete mixture. (30th October 2020) - Ong, Ghim Ping; Jagadeesh, Ajayshankar; Su, Yu-Min
Highlights: Pervious concrete pore properties are studied using XRCT and digital image processing. CFD-based non-Darcy permeability simulation model is developed and validated. Effect of XRCT parameters on pervious concrete non-Darcy permeability is studied. Abstract: Pervious concrete is a special class of concrete with sufficient continuous void structure resulting in the increase of drainage, skid resistance and acoustic characteristics. The paper attempts to investigate the effect of pore network properties obtained using advanced image processing techniques on the non-Darcy permeability characteristics of pervious concrete samples obtained from the same batch mixing process. Twelve different pervious concrete samples for a single pervious concrete mixture were produced in the laboratory using batch mixing and its internal pore network structure was obtained using medical X-ray computed tomography (XRCT) and digital image processing. The pore network structure from the XRCT scan is then adopted into a finite-volume computational fluid dynamics permeability simulation model to evaluate how pore network characteristics can affect non-Darcy permeability coefficients. The key microstructural parameters of the pervious concrete air voids and solids were analyzed in the paper, and it was found that an increase in non-Darcy permeability coefficient can be attributed to higher effective porosity, mean effective pore volume, throat area and coordination number properties. Overall, the findings presented in the paper can help in future optimization of pervious concrete mixture design and provide an understanding towards future works on pavement mixture quality control.